The Analyzing COVID-19 on a Global Scale: Investigating its Worldwide Ramifications - Mustapha Abdulsalam; Khadija Muntaqa Tijjani Usman; Amina Abdulkadir Nurudeen; Fatima Yusuf Muhammad (MultiTech Publisher, 2023)
The most recent coronavirus information and updates, including the number of confirmed cases, deaths, and affected countries worldwide, are outlined in this study. There were approximately 700 million confirmed cases and 6 million deaths globally at the time of the study. To manage and prevent the virus from spreading, the World Health Organization (WHO) has established guidelines and recommendations for safety measures like vaccination, wearing face masks, avoiding social situations, maintaining proper hand hygiene, and restricting travel. The emergence of novel virus variants highlights the need for ongoing vigilance and adaptation in public health, and ongoing research has guided the development of effective vaccines and treatments.